IMPLEMENTATION OF EDUCATION BUSINESS MANAGEMENT IN BANDAR LAMPUNG - Oki Dermawan; Ayu Wulandari; Adri Efferi; Alhamuddin Alhamuddin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
The educational institution of Al-Kautsar High School Lampung is an independent institution and carries out several business units. Researchers, in this case, research to find out about the implementation of business management education in Al-Kautsar High School. The type of research used is qualitative. They are collecting data using observation, interviews, and documentation and testing the validity of the data using source triangulation techniques. The results showed that Al-Kautsar High School is an educational institution capable of becoming an independent academic institution. This can be proven by business applications such as canteen, AK water, tutoring, outbound, and umrah. The income from these business units is used to repair, add, and maintain facilities and infrastructure. Private educational institutions have benefited from the implementation of these efforts.